2007
DOI: 10.1002/bit.21596
|View full text |Cite
|
Sign up to set email alerts
|

High‐density transfection with HEK‐293 cells allows doubling of transient titers and removes need for a priori DNA complex formation with PEI

Abstract: Recombinant proteins are of great commercial and scientific interest. Yet, most production methods in mammalian cells involve the time- and labor-consuming step of creating stable cell lines. Production methods based on transient gene expression are advantageous in terms of speed and versatility; yet, depending on the transfection protocol, transient transfection faces some bottlenecks such as a priori complex formation, limitations in terms of transfection and production media used and the need for medium exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 19 publications
6
117
1
3
Order By: Relevance
“…Compared with the standard two-step process, which requires an additional sterile vessel to premix PEI and DNA and then transfers the content into a bioreactor without sterile filtration (PEI/DNA particles cannot be sterile filtered), in situ complex formation is more amenable to upscaling and GMP compliance because of the lower contamination risk and easier handling involved. Research has suggested that in situ PEI/DNA complex formation can achieve higher reproducibility as small changes in maturation time can have a significant impact on titers (Backliwal et al 2008). In the present study, a higher transfection efficiency was obtained with the one-step transfection procedure.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…Compared with the standard two-step process, which requires an additional sterile vessel to premix PEI and DNA and then transfers the content into a bioreactor without sterile filtration (PEI/DNA particles cannot be sterile filtered), in situ complex formation is more amenable to upscaling and GMP compliance because of the lower contamination risk and easier handling involved. Research has suggested that in situ PEI/DNA complex formation can achieve higher reproducibility as small changes in maturation time can have a significant impact on titers (Backliwal et al 2008). In the present study, a higher transfection efficiency was obtained with the one-step transfection procedure.…”
Section: Discussionsupporting
confidence: 47%
“…A new and simpler method of TGE without priori formation of the PEI/DNA complex has been reported recently, and it has been confirmed to be better than a priori complex formation under certain conditions (Backliwal et al 2008). In the present study, we found that a one-step transfection process could produce higher transfection efficiency compared with the standard two-step process; however, there is no significant difference in GFP expression between these methods.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations